Enhancing Students’ Mathematical Representation Ability Using the Concrete-Pictorial-Abstract Approach - Azmidar, Azmidar; Darhim, Darhim; Dahlan, Jarnawi Afghani (FKIP Universitas Lampung, 2021)
Mathematical representation ability is basic for others’ mathematical ability, such as understanding ability, communication ability, reasoning ability, and problem-solving ability. The purpose of this research was to analyze the enhance students’ mathematics representation ability using the Concrete-Pictorial-Abstract Approach in the group (CPA-G) based on prior mathematical ability. The research method used the quasi-experimental with pre-response and post-response design. The population of this research was students grade VII. This research uses two classes which selected purposely, an experimental group that receives CPA-G and a control group that received regular learning (RL). Prior mathematical ability and mathematical representation ability tests were used as an instrument in this research. The result shows that the mathematical representation ability of students in high and middle of prior mathematical ability category, who received CPA-G higher than students who only received RL. This approach can enhance students’ mathematical representation ability, especially on the visual and symbolic representation. Keywords: The Concrete-Pictorial-Abstract approach in the group, mathematical representation ability, quasi experimental research DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp67-76